Modernism à la mode : fashion and the ends of literature - Sheehan, Elizabeth M. (Ithaca : Cornell University Press, 2018)
"This book puts the work of early twentieth-century texts in conversation with twenty-first-century theories of affect, materiality, animality, beauty, and history and explores how fashion describes the limits and possibilities for modernist aesthetic and political transformation"--
Introduction : fashioning modernism -- Moods, modes, modernism : reading fashionably with Virginia Woolf -- Material concerns : D.H. Lawrence, garments, and the matter of fiction -- This great work of the creation of beauty : imagining in W.E.B. Du Bois's Dark princess and black beauty culture -- Prophets and historicists : F. Scott Fitzgerald and Paul Poiret -- Coda : the pedagogies of fashion and modernism.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on October 24, 2018).
JSTOR
Keywords: English fiction -- 20th century -- History and criticism; American fiction -- 20th century -- History and criticism; Fashion in literature; Modernism (Literature) -- Great Britain; Modernism (Literature) -- United States; Roman anglais -- 20e siècle -- Histoire et critique; Roman américain -- 20e siècle -- Histoire et critique; Modernisme (Littérature) -- Grande-Bretagne.; Modernisme (Littérature) -- États-Unis.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; DESIGN -- Fashion; American fiction; English fiction; Fashion in literature; Modernism (Literature); Great Britain; United States; 1900-1999; Criticism, interpretation, etc